pilot study of combined transvertebral magnetic and transcutaneous stimulation for the rehabilitation of combat acute spinal cord injuries - Oleksandr Kulyk; Ivan Mazurchuk; Valeriia Polousova; Anna Pshenychna; Oksana Yarmolenko (Journal of Rehabilitation Medicine - Clinical Communications, 2025)
Aim of the study: To improve the effectiveness of neurorehabilitation in patients with severe combat spinal cord injury by combining spinal cord repetitive transvertebral magnetic stimulation (rTvMS) and non-invasive transcutaneous electrical stimulation (TcES) of peripheral nerves.